Kepimpinan Sekolah Visioner Dalam Meningkatkan Kemandirian Guru Di Smait At-Taisiriyah - Fahmi Muhamad Aziz; Mulyawan Sofwandy Nugraha (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2023)
The aims of this study were (1) the role of visionary school leadership in increasing teacher independence at SMAIT AT-Taisiriyah (2) the supporting and inhibiting factors for the role of visionary school leadership in increasing teacher independence at SMAIT AT-Taisiriyah. This research method uses qualitative methods using a descriptive approach. This method describes and explains by providing answers to the problem. The object of this research is the principal. Based on the results of the research and discussion carried out at SMAIT AT-Taisiriyah Cijengkol, Caringin District, Sukabumi Regency, visionary leadership is characterized by having the ability to make clear plans to achieve success. . With the formulation of a vision that can foster creativity, togetherness in professional development. The principal at SMAT At-Taisiriyah tries to provide motivation and provide good role models in the school environment. The Supporting Factors a) The high sense of togetherness and kinship that is intertwined in the school environment. b) Providing incentives/rewards and awards for educators who carry out their duties very well, and Inhibiting Factors a) The existence of honorary teachers, this has an effect on the low income of honorary teachers. So that it affects the teacher's performance, not optimal in providing the best service for the school